Prototype of landslide detection alarm based on IoT (Internet of Things) as a physics learning medium - Anisa, Nabila Putri; Rahman, Nor Farahwahida Binti Abdul; Saehana, Sahrul (Journal of Environment and Sustainability Education, 2024)
This research aims to create a prototype device in the form of an alarm capable of detecting landslide disasters in Donggala Regency. It is expected to be utilized in the environmental physics subject at the secondary school level. The study utilizes long-range communication (LoRa) and Telegram application as an early warning notification system for landslide disasters. The research method adopts the Research and Development (R&D) design adapted from Sugiyono's development research, consisting of potential and problems, data collection, product design, design validation, product testing, analysis, and reporting. The survey was employed as a data collection instrument. The quality or feasibility of the developed prototype, based on expert validation, indicates a "Very Good" category, and students' responses to the tool testing also show a "Very Good" category. Thus, the IoT-based landslide detection alarm prototype has been well-developed and is suitable for use in physics education at the secondary school level.